Pengaruh Internal Governance terhadap Manajemen Laba Aktivitas Rill dengan Kepemilikan Institusional sebagai Variabel Pemoderasi - Carolyn Lukita (Universitas Negeri Padang, 2022)
This study examines the effect of good corporate governance (GCG) on real earnings management. This study uses internal governance variables that have not been studied much related to GCG variables, internal governance is the check and balance process from subordinate executives (KSE), namely managers who are one level below the CEO. The sample in this study was taken from all sectors listed on the IDX in 2017-2019. This study also uses institutional ownership as a moderating variable. The results show that internal governance has a negative effect on real earnings management. Institutional ownership has also been shown to moderate the effect The results of this study provide a new suggestion regarding how to mitigate real earnings management actions by stakeholders.Keywords: Internal Governanace, Real earnings managemen, Abnormal Discretioner, Institutional ownership.